2008
DOI: 10.1097/jto.0b013e3181753b4b
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial Comparing Paclitaxel Poliglumex (CT-2103, PPX) in Combination with Carboplatin Versus Standard Paclitaxel and Carboplatin in the Treatment of PS 2 Patients with Chemotherapy-Naïve Advanced Non-small Cell Lung Cancer

Abstract: PPX/carboplatin failed to provide superior survival compared with paclitaxel/carboplatin in the first-line treatment of PS 2 patients with NSCLC, but the results with respect to progression-free survival and overall survival were comparable and the PPX regimen was more convenient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
88
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(88 citation statements)
references
References 19 publications
0
88
0
Order By: Relevance
“…However, the combination of CT-2103 and carboplatin was not superior to PTX and carboplatin in a randomized Phase III trial in patients with lung cancer. 22 Furthermore, PGA-PTX has not been reported to self-assemble into nanoparticles. In our study, a new nanoconjugate platform, PGG-PTX, was designed and synthesized without utilizing diblock copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…However, the combination of CT-2103 and carboplatin was not superior to PTX and carboplatin in a randomized Phase III trial in patients with lung cancer. 22 Furthermore, PGA-PTX has not been reported to self-assemble into nanoparticles. In our study, a new nanoconjugate platform, PGG-PTX, was designed and synthesized without utilizing diblock copolymers.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review indicated a median progression-free survival (PFS) of 8-13 months for patients with EGFRm-positive NSCLC receiving first-line EGFR TKIs 19 . In contrast, median time to progression or PFS for patients receiving platinum-based doublet chemotherapy combinations was 4-6 months [20][21][22][23] . The National Comprehensive Cancer Network (NCCN) guidelines recommend first-line therapy with an approved TKI for treatment of EGFRm-positive NSCLC 4 .…”
Section: Introductionmentioning
confidence: 99%
“…They are based on the traditional cytotoxic drugs (e.g. platinates [145,146], doxorubicin [147,148], camptothecin and analogues [149][150][151][152][153][154][155][156][157][158][159], paclitaxel/docetaxel [160][161][162][163][164], methotrexate [165], and irinotecan [166,167]). Xyotax (CT-2103 or OPAXIO), a PGA-paclitaxel conjugate, and NKTR-102, a polymer conjugate of irinotecan, are both currently in phase III clinical trials, being the conjugates closest to approval and market availability [164,[166][167][168].…”
Section: Polymer Therapeuticsmentioning
confidence: 99%